Pengaruh Teknologi Deepfake terhadap Kredibilitas Berita dan Jurnalistik - Irsyad, Irsyad (Komunika : Jurnal Ilmiah Komunikasi, 2025)
This raises concerns about the credibility of news and journalism, as deepfakes can be used to spread false information and manipulate public opinion. The purpose of this study is to discuss the impact of deepfake technology on news credibility, to compare it with previous research, and to evaluate the relevance of the findings to the current journalistic context. This study has important implications for journalism practitioners in facing new challenges from this technological advancement. The purpose of this study is to analyze the impact of deepfake technology on news and journalism credibility. Data collection methods used in this study include surveys, interviews, field experiments, and participant observation. Data analysis was carried out using descriptive statistical techniques and inferential analysis. Data from the survey and field experiments will be processed and analyzed to determine the level of change in perceptions of news credibility along with the use of deepfake technology. The results of the study indicate that deepfake technology has a significant impact on news and journalism credibility. According to the data collected, the use of deepfake in news production has led to a decline in public trust in the information presented by the media. In addition, these findings also highlight the importance of regulation and control in the application of deepfake technology in journalism to minimize the risk of spreading fake news and information manipulation. This emphasizes the need for a cautious approach to the use of technology that can damage the integrity of information and disrupt the fair and accurate reporting process. Cooperation between the media, government, and technologists is needed to overcome the negative consequences of deepfake in journalism. All parties must be responsible for ensuring the truth and fairness in presenting information to the public.